Kinerja Satpol PP dalam Upaya Mewujudkan Ketertiban Umum di Kota Sukabumi - Yulia Yulia; Ike Rachmawati; Andi Mulyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this research is to find out how the performance of Satpol PP in an effort to realize public order in the City of Sukabumi. This study uses Bernardin and Russel's grand theory and is a type of descriptive research with a qualitative approach, using purposive sampling techniques. In preparing primary data, researchers obtain data from the field, which is sourced from interviews and observations with respondents. Based on research results, the performance of Satpol PP in an effort to realize public order in Sukabumi City is still very far from success because the goal of Satpol PP in an effort to realize public order in the City of Sukabumi in dealing with students who play truant is not yet perfect or approaching the expected goals as what is desired by policy makers, and the resources in the Sukabumi City Satpol PP Office are still not enough, while the number of problems that exist in public order in the City of Sukabumi is so numerous and extensive. And Cooperation has not gone well because the community only relies on the actions of Satpol PP. Keywords: Performance, Public Order.